Back Cover: Synthesis, Structural Characterization, and Crystal Packing of the Elusive Pentachlorinated Azafullerene C59NCl5 (Chem. Eur. J. 38/2017). Issue 38 (2nd May 2017) - Amsharov, Konstantin Yu.; Holzwarth, Johannes; Roshchyna, Kateryna; Sharapa, Dmitry I.; Hampel, Frank; Hirsch, Andreas
Abstract : The azafullerene pentachloride C59 NCl5 obtained by high temperature halogenation of (C59 N)2 displays unprecedented and effective supramolecular bonding to the fullerene "surface". The cumulative effect of five chloro‐π interactions leads to an effective 1D host–guest stacking in the solid state. The pentachlorinated addition pattern serves as a "receptor" of the bowl‐shaped corannulene fragment and thus appears to be prospective for possible recognition of fullerenes and related geodesic PAH structures. More information can be found in the Communication by K. Yu. Amsharov, A. Hirsch et al. onpage 9014 .